ABUNDANCE AND DISTRIBUTION OF PENAEID LARVAE AS AN INDEX OF PENAEID PRAWN RESOURCES OF THE INDIAN OCEAN - Paulinose, V T; George, M J (Indian Journal of Fisheries, 2011)
Andysis of the data on the abundance of larvae of penaeids in 1927 plankton samples collected from the Indian Ocean during the International Indian Ocean Expedition (1960-1965) has shown that these larvae are more commonly represented in the area nearer the coast as indicated in the preliminary observations by Menon et al (1967).